Comparative Study Balance of The Heart ibn Qayyum Al-Jawziyyah with Collective Unconsciousness the Collective Unconscious Carl Gustav Jung - Hadziq, Abdulloh; Cem, Caroline; Sophie, Beguin; Sophie, Vandenhove (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The purpose of writing in this study is to describe the concepts presented by Ibn Qoyyum and Carl Jung about human perfection and tranquillity. the research is a qualitative study with a library research method. Ibn Qayyum explains that the health and safety of the soul is born if a person is able to balance the inner dimension and the physical dimension. while Carl Jung argues that a person's disconnection from collective unconsciousness can cause a person to spiritual dryness, existential dryness, and soul shock.